English Phonological Errors in Pronouncing Similarly-Spelled Words by Linguistics III Class Students - Sanger. A; Lumoindong. B (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Phonological errors in pronunciation are common practices not only among beginners who just started to learn English but also among English major students who have been dealing with English study for many years. While speaking in English as a second language in formal situations, they often mispronounce words with similar spellings. This study investigated how the pronunciation of English learners was influenced by words with the same spelling. The participants were the Linguistics III students from the English Department of the Faculty of Education at Klabat University. They were required to pronounce a list of commonly mispronounced words. The results of this research showed that the students frequently mispronounced words with similar orthography. These phonological errors were prevalent among English learners, including those majoring in English.